Use of Intramuscular Ephedrine Sulfate During Kidney Transplantation - Patel GP; Smith SA; Romej M; McAdoo B; Wilson EA (Dove Medical Press, 2023)
Gaurav P Patel, Susan A Smith, Michelle Romej, Billynda McAdoo, Elizabeth A Wilson Department of Anesthesiology, Emory University School of Medicine, Atlanta, GA, 30322, USACorrespondence: Gaurav P Patel, Department of Anesthesiology, Emory University School of Medicine, 1364 Clifton Road, NE, Atlanta, GA, 30322, USA, Tel +1 404-778-3900, Email gppatel@emory.eduAbstract: Hypotension during kidney transplantation can be common. Vasopressor use during these procedures is often avoided, with a fear of decreasing renal perfusion in the transplanted kidney. However, adequate perfusion for the rest of the body is also necessary, and given that these patients often have underlying hypertension or other comorbid conditions, an appropriate mean arterial pressure (MAP) has to be maintained. Intramuscular injections of ephedrine have been studied in the anesthesiology literature in a variety of case types, and it is seen as a safe and effective method to boost MAP. We present a case series of three patients who underwent renal transplantation and who received an intramuscular injection of ephedrine for hypotension control. The medication worked well for increasing blood pressures without apparent side effects. All three patients were followed for more than one year, and all patients had good graft function at the end of that time period. This series shows that while further research is necessary in this arena, intramuscular ephedrine may have a place in the management of persistent hypotension in the operating room during kidney transplantation.Keywords: kidney transplant, hypotension, general anesthesia, intramuscular ephedrine, perfusion pressure